2019
DOI: 10.1002/14651858.cd004780.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Family therapy approaches for anorexia nervosa

Abstract: Analysis 1.2. Comparison 1 Family therapy approaches vs standard care/treatment as usual, Outcome 2 Remission long-term follow-up..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 165 publications
1
35
0
Order By: Relevance
“…This review (Fisher 2019) was an update of the original version (Fisher 2010) that increased the number of included studies from 13 to 25 and the number of comparison analyses from 6 to 12. This meant that there was a large spread of analyses rather than a strengthening of evidence in the major comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review (Fisher 2019) was an update of the original version (Fisher 2010) that increased the number of included studies from 13 to 25 and the number of comparison analyses from 6 to 12. This meant that there was a large spread of analyses rather than a strengthening of evidence in the major comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane Review by Fisher et al (2019) aimed to assess the efficacy of different family therapy approaches compared with other treatments for anorexia nervosa, by investigating whether family therapy reduces rates of anorexia nervosa or associated symptoms. This review was an update of an earlier Cochrane Review (Fisher 2010), which suggested, from limited evidence with potential bias problems, that family therapy may be more effective than treatment as usual in the short term.…”
Section: The Clinical Questionmentioning
confidence: 99%
“…This nding is relevant for clinical work highlighting the importance of focusing on relationships and trauma in the treatment of individuals with AN. Interventions, such as family therapy, aim to target some of these factors, namely family dynamics, and there is some evidence that family therapy can be effective in promoting remission (Fisher et al, 2019). It would be of interest to build on these ndings and examine the effectiveness of interventions that target social relationships and complex trauma more broadly, reaching outside of the immediate family.…”
Section: Research and Clinical Implicationsmentioning
confidence: 99%
“…Regardless of current treatments, the mortality rate from anorexia nervosa has remained constant (Birmingham et al, 2005;Signorini et al, 2007). Besides family therapy for medically stable adolescents, either in conjoint or separated formats (Fisher et al, 2018), the current spectrum of evidence-based AN treatments ranges from specialized brand type treatments (enhanced-cognitive behavior, psychodynamic, and interpersonal therapy) to new faceted treatments customized to tap the specific characteristics of patients, as is the case of the Maudsley Model of Anorexia Treatment in Adults, MANTRA (Schmidt et al, 2012). However, several randomized control trials have shown the "dodo verdict" prevails since none of these treatments was superior to the others (Gutiérrez and Carrera, 2018;van den Berg et al, 2019).…”
Section: New Perspectives To Unlock the Current Impasse In Treating Amentioning
confidence: 99%